An interdisciplinary review of current and future approaches to improving human-predator relations - Pooley, S; Barua, M; Beinart, W; Dickman, A; Holmes, G; Lorimer, J; Loveridge, A; Macdonald, D; Marvin, G; Redpath, S; Sillero-Zubiri, C; Zimmermann, A; et al. (Wiley, 2017)
In a world of shrinking habitats and increasing competition for natural resources, potentially dangerous predators bring the challenges of coexisting with wildlife sharply into focus. Through interdisciplinary collaboration between authors trained in the humanities, social sciences and natural sciences, this paper offers a review of current approaches and a vision for future approaches to understanding and mitigating adverse human-predator encounters. The paper first reviews some limitations to current approaches to mitigation. Second, it reviews an emerging interdisciplinary literature, identifying key perspectives on how to better frame and therefore successfully mitigate such conservation conflicts. Third, it discusses the implications for future research and management practice. It is concluded that a demand for rapid, ‘win-win’ solutions for conservation and development favours dispute resolution and technical fixes, obscuring important underlying drivers of conflicts. Without due cognisance of these underlying drivers, our well intentioned efforts, focussed on ‘human wildlife conflicts,’ will fail.